The Effect Of Psychological, Physiological, And Time Aspects Of Qris Usage On Consumer Satisfaction From The Perspective Of Islamic Business Ethics (A Study Of Clothing Stores At Simpur Center, Bandar Lampung) - Indah Dwi Permata; Madnasir Madnasir; Ahmad Habibi (Universitas Islam Negeri Mataram, 2025)
This study aims to examine the effects of psychological, physiological, and time-related aspects of Quick Response Code Indonesian Standard (QRIS) usage on consumer satisfaction from the perspective of Islamic business ethics. The research employs a quantitative approach using a survey method. Data were collected from 100 consumers who used QRIS at clothing stores in Simpur Center, Bandar Lampung. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software.The results indicate that the psychological aspect has a positive and significant effect on consumer satisfaction, highlighting the importance of trust, security, and comfort in digital transactions. The physiological aspect also shows a significant influence, although with a relatively lower magnitude, which is associated with ease of use, interface clarity, and system responsiveness. In addition, the time aspect significantly affects consumer satisfaction, as transaction efficiency and speed enhance convenience and reduce waiting time. Simultaneously, these three aspects exert a significant influence on consumer satisfaction, explaining 67 percent of the variance.From the perspective of Islamic business ethics, the implementation of QRIS reflects the principles of justice, transparency, responsibility, and public benefit (maslahah), thereby supporting the provision of secure, fair, and efficient transaction services. This study concludes that optimizing QRIS usage in line with Islamic business ethics values has the potential to enhance consumer satisfaction and support the sustainability of digital payment systems.